A numerical investigation and probabilistic analysis of excavation earth retaining wall instability caused by underground pipeline leakage. (November 2021) - Ji, Jian; Xia, Jiacheng; Zhang, Zheming; Fu, Guoyang; Kodikara, Jayantha
Abstract: In recent years, underground pipeline leakage occurs frequently in urban regions, which seriously reduces the soil-structure stability in the vicinity of the leakage. In this paper, a numerical study about pipeline leakage-induced instability of adjacent excavation earth retaining wall (EERW) is carried out. To reflect the phenomenon of soil strength degradation when encountering leakage water, the relationship between soil strength parameters and saturation is established by using an empirical formula, which is then implemented in Abaqus via the USDFLD subroutine. After verifying the proposed simulation method, the instability time of EERW under different burial depths of the leakage pipeline is presented. In order to reflect the influence of underlying geotechnical uncertainties on the EERW performance and to improve the probabilistic computational efficiency, the neural network is used as a surrogate model to replace the tedious finite element modeling, and Monte Carlo Simulation (MCS) is used to calculate the time-dependent failure probability of the retaining structure. Extensive sensitivity analyses are carried out to explore the effect of random variables on the failure probabilities. Compared with the unsaturated soil permeability coefficient, the increase of the initial pipeline pressure has more pronounced influence on the stability of EERW, and the initial saturation shows completely different forms in the early and late stages of water leakage.